Alimentación de un motor monocilíndrico con hidrógeno obtenido a través de la electrólisis del agua. - López Villacres, Juan Carlos (2018)
Its design was built in a dry electrolytic cell (hydrogen generator), using a highly-resistant to corrosion material as the stainless steel to give place to elements which work as a positive, negative and neutral charge. This device operates with a twelve- volts tension obtained from a vehicle battery through this runs an electrolyte which uses a sodium hydroxide solution to improve the driving of energy through water given place to a phenomenon called electrolysis. The electricity decomposes the water into two atoms of hydrogen and an atom of oxygen obtaining in this way the hydrogen combustible that will serve as fuel for an engine. Afterwards, the hydrogen gas was stored to be directly supplied to the feeding system of a Honda four-stroke engine of thirty-five -cubic cylinders. Consecutively was built a prototype where the components and necessary systems to start this kind of engine were implemented. Once the system was installed and with the purpose of analyse the effects of hydrogen fuel towards the engine, two tests of gas leakage were carried out. The first proof was done with the engine running on gasoline. While in the second proof hydrogen combustible was employed as motor fuel. In this way the behaviour of gas leakage was evidenced with both fuel in order to evaluate the incidences produced by the use of hydrogen gas as fuel.